Convolutions of Bernoulli and Euler Polynomials - Chu, Wenchang; Zhou, Roberta R. (Sarajevo Journal of Mathematics, 2024)
By means of the generating function technique, several convolution identities are derived for the polynomials of Bernoulli and Euler. 2000 Mathematics Subject Classification. Primary 11B68, Secondary 05A15